1997
DOI: 10.1002/anie.199713901
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Beam Studies on Semiconductor Clusters: Polarizabilities and Chemical Bonding

Abstract: Schematic representation of a semiconductor cluster isolated in the molecular beam during the flight though an electric Stern-Gerlach field. The cluster flies with a velocity v parallel to the cylindrical bent electrode surfaces, which can be seen in the cross section. The field induces a dipole moment in the cluster that is proportional to the polarizability. Owing to the well-defined inhomogeneity of the field a somewhat larger force is exerted on the negative partial charge than on the positive. The resulti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
11
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(12 citation statements)
references
References 57 publications
1
11
0
Order By: Relevance
“…The optical properties of semiconductor clusters are currently a research subject of advanced scientific and technological interest. 1,2 The electric polarizability of silicon clusters in particular have been extensively studied both experimentally [3][4][5][6][7] and theoretically. [8][9][10][11][12][13][14][15][16][17][18][19][20][21] Most of the above studies focus on the dipole polarizability.…”
Section: Introduction and Theorymentioning
confidence: 99%
“…The optical properties of semiconductor clusters are currently a research subject of advanced scientific and technological interest. 1,2 The electric polarizability of silicon clusters in particular have been extensively studied both experimentally [3][4][5][6][7] and theoretically. [8][9][10][11][12][13][14][15][16][17][18][19][20][21] Most of the above studies focus on the dipole polarizability.…”
Section: Introduction and Theorymentioning
confidence: 99%
“…The dipole polarizability, however, represents a suitable molecular property that can take on the role of the dielectric constant and can be measured without touching the cluster. 1 The dipole polarizability comprises the information of the bonding character in the cluster, and on the other hand, through the Classius-Mosotti relation it yields information about the dielectric constant of the solid-like macroscopic particle formed with the cluster. The experimental measurement of cluster polarizabilities is relatively easy in comparison to other properties of neutral clusters.…”
Section: Introductionmentioning
confidence: 99%
“…The chemical bonding is profoundly changed in the formation of a cluster whereas the solid-state-like properties like the dielectric constant are of no significance in a cluster of few atoms. The dipole polarizability, however, represents a suitable molecular property that can take on the role of the dielectric constant and can be measured without touching the cluster . The dipole polarizability comprises the information of the bonding character in the cluster, and on the other hand, through the Classius−Mosotti relation it yields information about the dielectric constant of the solid-like macroscopic particle formed with the cluster.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such variations are due to discontinuous changes in electronic/geometric structures, and much effort has been put into correlating these structural attributes to observed physical and chemical properties. [10][11][12] The potential value of polarizability measurements for cluster isomer identification has been recognized by Moullet et al 13 In this paper, the static dipole polarizabilities of nickel clusters (N 12 -N 58 ), obtained via electric field deflection measurements, are presented. For example, molecular beam-based electric deflection measurements have shown that the polarizabilities of pure and mixed alkali metal clusters [5][6][7][8] and aluminum clusters 9 display variations that can be correlated to features in geometric and/or electronic structures.…”
Section: Introductionmentioning
confidence: 87%